Influence of Individual Characteristics, Training and Supervision on Work behavior - Widyastuti, Titing; Sitorus, Irwan; Besar Agung Martono; Felina C. Young (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of the study was to determine partially the effect of individual characteristics on training and supervision of work behavior in the operational department of environmental management companies in Bogor. Based on the findings of individual characteristics, training, and monitoring aspects that affect the work behavior of Bogor's environmental management company, the results of regression equation Y = 9.369 + 0.268 X1 + 0.454 X2 + 0.211 X3 and R² = 0.764 It's a useful model. As a predictor, we can conclude that: First, there are the effects of individual traits that have a positive and significant positive impact on work behavior. Second, there is the impact of education, which has a positive and significant impact on work behavior. Third, there is the influence of the director, which has a positive and important influence on the behavior of work